“Los límites del honor”. Nobility and Hierarchies in Brazil, New Spain and Peru, 17th and 18th Centuries - Raminelli, Ronald (Revista Complutense de Historia de América, 2014)
This article aims toward a comparative study of the American nobilities (Brazil, Peru and New Spain) between the 17th and 18th centuries. The central themes of this research are the nobles’ strategies for upward social mobility and their political involvement in the militia and municipal offices. Titled nobles, knights and “hidalgos” lived in Peru and New Spain. In Brazil, noble presence was limited to “fidalgos” and knights that didn’t necessarily possess noble qualities. The incidents discussed here show that the American nobilities possessed considerably weak privileges that were constantly seen as threats to the colonial order.